English in rural Bangladesh. (11th November 2014) - Erling, Elizabeth J.; Seargeant, Philip; Solly, Mike
<x content-type="archive" xml:space="preserve">Abstract</x> English's elevated status within a global economy of languages means that English-language education is increasingly promoted in international development initiatives in countries such as Bangladesh. This is partly due to a growing conviction that English is able to play an important role in helping people participate in global economic markets from which they have previously been excluded (Seargeant & Erling, 2011). Despite the strong associations made between English-language ability and development, there is at present only limited evidence showing a causal relationship between the two (Erling, forthcoming), while a complex of other issues surrounding the cultural politics of the language also play a role in the social implications of its promotion in such contexts. The aim of this article is to examine how English is perceived in rural Bangladesh by the people at whom such international development programmes are targeted. A broad assumption of such programmes is that English is a positive and, in some sense, necessary resource for development. The article investigates whether this matches the perception of those at whom such projects are aimed, and what it is that these communities feel the language can offer both in practical and in socio-cultural terms for the developmental challenges they face. In order to examine these questions the article draws on results from an ethnographical survey of two rural areas in Bangladesh which investigated the attitudes and aspirations of local community members to the potential impact of English-language education on their social prospects and cultural identities.